Issues of Gender, Child Protection and Human Rights in Islamic Family Law in The Archipelago - Khaldun, Rendra (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
In the idiom of the Islamic legal tradition, gender equality is a new problem (masā'ilmustahdatha). Gender equality is an issue that was not found in Islamic law until the 20th century. By the middle of the century, through the CEDAW convention, gender equality gained a clear international mandate. Many Muslim countries ratify CEDAW (except Iran, Somalia and Sudan). Although in fact, the ratification was accompanied by a reservation that spoke of tensions that have not been resolved until now, therefore the United Nations by echoing freedoms based on human rights and UNICEP echoing about the protection of children so that children get their rights in living life so that later they will not be marginalized, in Indonesia itself a law on child protection was formed that gives children legal power in all forms discrimination both in the family environment and in the community itself and in the end children are free to create without any bullying against them. In CEDAW, article 5 emphasizes eliminating all forms of discriminatory treatment in the private sphere, namely the family, which according to CEDAW is the most important and frequent place of injustice against women's human rights. Human rights (HAM) and Islamic family law have the same goal in protecting and guaranteeing the welfare of individuals and families. However, the way they are applied and interpreted can be different. The integration of human rights in Islamic family law includes the understanding that human rights principles, such as equality, freedom, and protection from discrimination, must be applied in the context of Islamic law. This understanding requires a balance between traditional norms and the demands of modern human rights.